‘It fitted in with our lifestyle’: an investigation into episodic volunteering in the tourism sector - Holmes, Kirsten (Routledge, 2014)
Tourism organizations are dependent on volunteers to deliver visitor services. Evidence suggests that volunteering is changing with a decline in volunteer hours per head and a rise in episodic forms of volunteering. This paper uses data from interviews with both regular and episodic volunteers in tourism-related roles to examine how volunteering fits within their working and leisure lives and how and why they make time for volunteering. The findings reveal that episodic volunteers are still passionate about the activity, but have different motives from regular volunteers who are seeking an ongoing activity with social benefits. Episodic volunteers often make a bigger time commitment in the short term and these intense roles would be difficult to sustain regularly. However, the interviews also identify that episodic volunteers are regular volunteers at other organizations and vice versa. This paper concludes by calling for a portfolio approach to researching volunteers.